Soil erosion- status, causes and preventive measures in Trans-Himalayan region of Leh-Ladakh in J&K - SINGH, R. K.; MOHARANA, P. C.; GOYAL, R. K.; BHATT, R. K.; RAGHUVANSHI, M. S.; MEENA, H. M. (Journal of Soil and Water Conservation, 2019)
Soils of the cold arid region of Leh-Ladakh are quite distinct from those of other regions due to differences in climate, topography, vegetation and rocks. Due to sloppy and rugged topography of the region, the extent of erosion varies from moderate to very severe. This article deals with the soil characteristics along with the processes involved in causing erosion. Existing soil erosion control measures have been deciphered alongside some prominent bio-engineering measures, which are required to mitigate the soil erosion process. The survey on vulnerability indicators related to soil properties and the status and potential of methods for soil conservation was conducted in Leh districts of J&K. The methodology adopted for assessment of the area was based on collection of data by observation of surface features during technical survey and by personal interviews of the local people using questionnaires. By and large, the soils are shallow to very shallow in depth. They vary widely in colour, texture, structure and permeability depending upon topography and vegetation. Depending on the soil properties, severity of erosion also varies from place to place.